Measuring temperature effects on nano-bubble growth in tungsten with grazing incidence small angle X-ray scattering. (August 2017) - Thompson, Matt; Doerner, Russ; Ohno, Noriyasu; Kirby, Nigel; Kluth, Patrick; Riley, Daniel; Corr, Cormac
Highlights: W samples were exposed to He plasma in the MAGPIE, NAGDIS-II and PISCES-A across a range of sample temperatures between 473–1123 K. GISAXS was used to quantify the effect of plasma fluence and W surface temperature on He nano-bubble size distributions. In NAGDIS-II at 873 K and Pisces-A at 643–673 K, nano-bubbles are exponentially distributed with mean diameters μ ≈ 0.5 nm. Above ∼900 K nano-bubbles followed an approximately exponential distribution with μ > 0.65 nm demonstrating a significant increase in nano-bubble sizes at higher temperatures. Abstract: W samples were exposed to He plasma in the MAGPIE, NAGDIS-II and PISCES-A across a range of sample temperatures between 473–1123 K. GISAXS was used to quantify the effect of plasma fluence and W surface temperature on He nano-bubble size distributions. In NAGDIS-II at 873 K nano-bubbles are exponentially distributed with mean diameters μ = 0.64 ± 0.01 nm, similar to the value of μ = 0.62 ± 0.01 nm found for the MAGPIE plasma device at the much lower temperature of 473 K. Above ∼900 K nano-bubbles followed an approximately exponential distribution with μ > 0.72 nm demonstrating a significant increase in nano-bubble sizes at higher temperatures.